Analisis Yuridis Penerapan Sanksi Pidana Terhadap Pelaku Tindak Pidana Pembalakan Liar Di Provinsi Papua Barat - Junaidi Bian (Jurnal Pendidikan Indonesia, 2025)
Illegal logging activities without regard to forest management principles to ensure the sustainability of forest resources have caused various negative impacts in various aspects, forest resources that have been destroyed during the New Order era, are increasingly damaged due to the rampant illegal logging in very large quantities. Losses due to illegal logging have broad dimensions not only to economic problems, but also to social, cultural, political and environmental problems. To anticipate forest damage that is carried out in various forms, it is necessary to enforce the law consistently against the perpetrators regardless of ethnicity, religion, and social status, because everyone must be treated equally before the law. The purpose of the study is to determine and analyze the impact of light criminal sanctions on illegal logging perpetrators in West Papua, to analyze the application of forestry criminal sanctions against illegal logging perpetrators according to Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction and to determine and analyze the role of indigenous peoples in maintaining forest sustainability in West Papua, and to analyze the judge's considerations in imposing sanctions on illegal logging perpetrators. This study uses a qualitative method, namely a way to obtain correct knowledge or truth through systematic steps. Qualitative data analysis in the form of a comprehensive explanation and description of the problems studied to be further stated in the form of a description to examine the application of criminal sanctions against illegal logging perpetrators, in order to obtain the data needed for the resolution and discussion as a whole in order to obtain scientific results, the author in compiling this study in order to facilitate and examine library materials or secondary data which include primary legal materials, secondary legal materials and tertiary legal materials. that forestry crimes can be categorized as extraordinary crimes or called Extra Ordinary Crimes, so that if the criminal sanctions given to the perpetrators are very light, it will certainly be a challenge in eradicating the activities in question. In addition, this also becomes a gateway for other parties who want to do the same thing because there is no fear of the punishment given.